Phototoxic target lipid model of single polycyclic aromatic hydrocarbons. (6th September 2016) - Marzooghi, Solmaz; Finch, Bryson E.; Stubblefield, William A.; Dmitrenko, Olga; Neal, Sharon L.; Di Toro, Dominic M.
Abstract: A phototoxic target lipid model (PTLM) is developed to predict phototoxicity of individual polycyclic aromatic hydrocarbons (PAHs) measured either as median lethal concentration (LC50) or median lethal time (LT50) for a 50% toxic response. The model is able to account for the differences in the physical/chemical properties of PAHs, test species sensitivities, and variations in light source characteristics, intensity, and length of exposure. The PTLM is based on the narcotic target lipid model (NTLM) of PAHs. Both models rely on the assumption that mortality occurs when the toxicant concentration in the target lipid of the organism reaches a threshold concentration. The PTLM is applied to observed LC50s and LT50s for 20 individual PAHs, 15 test species—including arthropods, fishes, amphibians, annelids, mollusks, and algae—exposed to simulated solar and various UV light sources, for exposure times varying from less than 1 h to 100 h, a total of 333 observations. The LC50 concentrations range from less than 0.1 µg/L to greater that 10 4 µg/L. The model has 2 fitting parameters that are constant and apply to all PAHs and organisms. The root mean square errors of prediction for log(LC50) and log(LT50) are 0.473 and 0.382, respectively. The results indicate that the PTLM can predict the phototoxicity of single PAHs over a wide range of exposure conditions and to organisms with a wide range of sensitivities. Environ Toxicol Chem 2017;36:926–937. © 2016 SETAC